2022
DOI: 10.1111/jerd.12865
|View full text |Cite
|
Sign up to set email alerts
|

The Aesthetic Contour Graft ‐ Enhancing peri‐implant soft tissue contours and pontic sites with guided bone regeneration

Abstract: Objective In this article, we will discuss strategies for enhancing peri‐implant soft tissue contours and pontic sites with hard tissue augmentation. Clinical consideration One of the keys to the esthetic illusion of an implant‐supported restoration is to create an ideal emergence profile. A critical part of any emergence profile is based on the height and thickness of the tissue surrounding the restoration and whether there are any defects in this tissue. Even when there is adequate bone in which to place imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…17 Whereas, some retrospective studies report that the thickness of soft tissue increase after facial bone tissue thickness increasing after GBR, improving implant esthetics, but the correlations needed further study. 18 The outcome in this study revealed that the alteration of labial bone thickness from 2.0 to 1.0 mm had insignificant difference on the effects on stress/strain distribution in the peri-implant bone tissue and implant's displacement. And the clinical result had indicated that soft tissue augmentation did effectively achieve satisfactory esthetic effects (Figure 7).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…17 Whereas, some retrospective studies report that the thickness of soft tissue increase after facial bone tissue thickness increasing after GBR, improving implant esthetics, but the correlations needed further study. 18 The outcome in this study revealed that the alteration of labial bone thickness from 2.0 to 1.0 mm had insignificant difference on the effects on stress/strain distribution in the peri-implant bone tissue and implant's displacement. And the clinical result had indicated that soft tissue augmentation did effectively achieve satisfactory esthetic effects (Figure 7).…”
Section: Discussionmentioning
confidence: 62%
“…12 At the same time, soft tissue augmentation as a less traumatic and more intuitive technology of tissue augmentation has gained increasing clinical traction. [13][14][15][16][17][18][19] As similar studies indicate that the labial bone mass is intimately connected to biomechanical results. 20 Nevertheless, the available data to estimate the minimal bone thickness to avoid over-loading resorption from the biomechanical perspective is limited.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…An alteration of the alveolar ridge contour following natural tooth loss compromises the esthetics and function of dental treatments, especially at the anterior part of the jaw [ 1 ]. The management of the tooth extraction site via the tissue regenerative approach is of interest as a new strategy in dental treatment.…”
Section: Introductionmentioning
confidence: 99%